The association between audit business scale advantage and audit quality of asset write-downs - Ziye Zhao; Bin Zhang (China Journal of Accounting Research, 2008)
This paper examines whether the scale advantage of auditing firms can be used as an alternative indicator of audit quality when the evaluation of audit quality is costly. The adoption of asset impairment recognition in China has brought about a considerable impact on financial reporting of Chinese listing companies in recent years. This new accounting practice provided a special environment, which was subjected to less endogeneity problems than usual, to test the relationship between the scale of auditing business and audit quality. Prior research reported empirical evidence that both market value and firm characteristics are empirically related to write-downs, reflected in the four dimensions return relevance, price relevance, persistence and determinant. Using these four dimensions, we investigated whether audit business scale advantage (ABSA) affect audit quality of asset write-downs. We contribute to the literature with the following findings. First, auditors' business scale is positively related to return relevance of write-downs. Second, auditors with ABSA not only enhance the relevance between impairments and economic variables but also weaken the relation between impairments and managerial variables; however, the results appear in only a few of the firm-specific variables. Third, results are mixed when we test the ABSA effect on price-relevance and persistence dimensions. Fourth, the ABSA effect is stronger when the complexity of asset write-downs requires some inside information to comprehend the nature of action. Adding to the main finding, we also found the ABSA effect became weaker when we proxy ABSA with raw data of companies' business scale instead of the top five auditors in business scale. Taken together, our results show that the ABSA effect does exist in auditing of assets write-downs, although with weak evidence. Our results also indicated rational auditor choice based on quality of service in China's audit market. We identified some unique factors from stakeholders' cooperative structuring actions in China audit market as potential explanations to the market rationality.
Keywords: 650; auditing; asset write-downs; accounting discretion